Penyuluhan Manajemen Beternak Itik untuk Meningkatkan Ketersediaan Bahan Baku Telur Asin - Mohammad Hasil Tamzil; Budi Indarsih; I Nyoman Sukartha Jaya; Ni Ketut Dewi Haryani; Asnawi Asnawi (Universitas Mataram, 2020)
The extension activity aimed to improve the duck farmer skills in duck farming system in Candi Manik village, Sekotong Sub-District, West Lombok District. The activity was successfully conducted due to collaboration among several parties, including village officials, KKN student of University of Mataram, and lecturers of Faculty of Animal Science University of Mataram. The activity was carried out using talk and discussion methods. All of the invited participants attended the activity until the end. The whole activity ran smoothly and in orderly manner. Materials presented during the activity were needed by the participants, especially the duck farmers. Thus, it can be concluded that, the extension activity was a success as it met the planned targets and objectives. Materials given were: breeding, feed and feeding, menegement of rearing sytem, disease and disease contole, and post-harvest handling management. All of the participants attended the extension activity until the end. The whole extension activities consisting of discussions, questions and answers sessions took place in an orderly manner. The discussed extension topics were material needed by participants, especially for duck farmers. Thus it can be concluded that the material provided can improve duck farming skills of the participants in order to increase egg production as salted egg raw materials